The Effect of E-Wallet and E-Money on Consumptive Behavior of the People of Bengkulu City - Muji Lestari; Ahmad Soleh; Suswati Nasution (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
The purpose of this study was to determine the extent of the influence of E-Wallet and E-Money on the consumptive behavior of the people of Bengkulu City. This research is quantitative descriptive. The method used is a questionnaire. The sample of this research is 100 respondents. The results showed that multiple linear regression obtained Y = 29.600 + 0.197 (X1) + 0.202 (X2) + 3.394, meaning that there was a positive or unidirectional relationship between E-Wallet (X1), and E-Money (X2) on the consumptive behavior of urban communities. Bengkulu. The results of the e-wallet test (X1) show tcount 4.019 > ttable 1.984 and a significance of 0.000 <0.05, then the results of the hypothesis Ha are accepted and Ho is rejected, meaning that e-wallet has a positive and significant effect on the consumptive behavior of the people of Bengkulu city. The results of the e-money test (X2) show tcount 3.186 > ttable 1.984 and a significance of 0.000 <0.05, then the results of the hypothesis Ha are accepted and Ho is rejected, meaning that e-money has a positive and significant effect on the consumptive behavior of the people of Bengkulu city. Furthermore, the result of the ftable value is 11.784 > 2.70, it is concluded that the hypothesis is accepted, meaning that there is a simultaneous effect between e-wallet (X1) and e-money (X2) on the variable of consumptive behavior (Y) of the people of Bengkulu city. This can be seen at the significance level of 0.000 < 0.05.